2021
DOI: 10.4103/jmau.jmau_69_20
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Evaluation of CDX2 and Ki67 in Colorectal Lesions with their Expression Pattern in Different Histologic Variants, Grade, and Stage of Colorectal Carcinomas

Abstract: Background: A variety of colorectal lesions are surgically treated encompassing both benign and malignant polyps and colorectal cancer (CRC). CRC is the third most common cause of death in developed countries. Over the last decade, CDX2 has been linked to CRC progression, with reduced expression of the protein associated with more advanced tumor stage, vessel invasion, and metastasis. Aims and Objectives: To analyze the histopathology and immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…In colorectal adenocarcinoma, present study showed 31 cases with 3+ grading of CDX2 expression which is similar to study conducted by Nayak et al 13 While in study conducted by Mesina et al 14 majority cases showed 2+ grading of CDX2 expression.…”
Section: Discussionsupporting
confidence: 89%
“…In colorectal adenocarcinoma, present study showed 31 cases with 3+ grading of CDX2 expression which is similar to study conducted by Nayak et al 13 While in study conducted by Mesina et al 14 majority cases showed 2+ grading of CDX2 expression.…”
Section: Discussionsupporting
confidence: 89%
“…So Ki-67 expression is an independent prediction factor of poor prognosis of colorectal cancer, with 50% Ki-67 expression defined as the critical value [ 10 , 27 , 28 ]. Currently, Ki-67 expression of rectal cancer was generally obtained through invasive biopsy or surgical pathology tissues [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower Ki-67 LI with medium intensity has been described in non-neoplastic polyps compared to neoplastic lesions [ 217 ]. In colorectal ADs, the Ki-67 expression was lower [ 218 ] or comparable to CRC [ 217 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
“…Lower Ki-67 LI with medium intensity has been described in non-neoplastic polyps compared to neoplastic lesions [ 217 ]. In colorectal ADs, the Ki-67 expression was lower [ 218 ] or comparable to CRC [ 217 ]. Moreover, a higher positive rate was observed in AD cases with high atypia and carcinoma in situ [ 219 ] and in more severe dysplastic adenomatous lesions [ 220 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation